Formal verification of object-oriented software International Conference, FoVeOOS 2010, Paris, France, June 28-30, 2010, Revised Selected Papers - Beckert, Bernhard; Marché, Claude (Springer, 2011)
This book presents the thoroughly refereed post-conference proceedings of the International Conference on Formal Verification of Object-Oriented Software, FoVeOOS 2010, held in Paris, France, in June 2010 - organised by COST Action IC0701. The 11 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 21 submissions. Formal software verification has outgrown the area of academic case studies, and industry is showing serious interest. The logical next goal is the verification of industrial software products. Most programming languages used in industrial practice are object-oriented, e.g. Java, C++, or C#. FoVeOOS 2010 aimed to foster collaboration and interactions among researchers in this area.